Factors Associated with Underweight among Two Years Old Children in DKI Jakarta Province (Indonesian Family Life Survey 2014) - Nabilla Atelya; Ratu Ayu Dewi Sartika; Winda Mulianingsih (Indonesian Journal of Public Health Nutrition, 2021)
Abstract A good health status, cognitive development, and productivity cannot be achieved without good nutrition. Nutritional status and its fulfilment of two years old children will be shaping the health status in the next age period. Unfortunately, nutritional problems like underweight is still a significant health problem in Indonesia, especially Special Capital Region of Jakarta. This study used secondary data achieved from Indonesian Family Life Survey 5 data in 2014. This study used a cross-sectional study design with a total of 135 samples of two years old children using a total sampling. Accordingly, the chi square test was used to find factors associated with underweight among two years old children. The result showed that the prevalence of underweight among under two years old children in DKI Jakarta Province was 30,4%. This result showed that child characteristics such as gestational age (OR= 5,813; CI= 1,291 - 26,178), low birth weight (OR= 5,060; CI= 1,136 - 22,533), and frequency of eating sweets (OR= 3,5; CI= 1,118 – 10,962) were associated with underweight (p-value < 0,05). The result of the study suggests that government should involve more in order to increase the role of community such as health center staff and cadres on preventing, detecting, and handling underweight cases by providing education and solutions to this phenomenon. AbstrakStatus kesehatan yang baik, perkembangan kognitif, dan produktivitas tidak dapat dicapai tanpa gizi yang baik. Status gizi dan pemenuhannya terhadap anak usia dua tahun akan mempengaruhi derajat kesehatan pada periode usia berikutnya. Sayangnya masalah gizi seperti kekurangan berat badan masih menjadi masalah kesehatan yang serius di Indonesia, khususnya di ibu kota negara, DKI Jakarta. Penelitian ini menggunakan data sekunder dari data Indonesia Family Life Survey 5 tahun 2014. Penelitian ini menggunakan desain studi cross sectional dengan jumlah sampel sebesar 135 bayi dua tahun menggunakan total sampling. Uji chi square digunakan untuk mengetahui faktor-faktor yang berhubungan dengan berat badan rendah pada anak usia dua tahun. Hasil penelitian menyatakan bahwa prevalensi anak dengan berat badan rendah pada balita di Provinsi DKI Jakarta sebesar 30,4%. Hasil penelitian ini menunjukkan bahwa karakteristik anak seperti usia kehamilan (OR= 5,813; CI= 1,291 - 26,178), BBLR (OR= 5,060; CI= 1,136 - 22,533), dan frekuensi makan yang manis berhubungan dengan berat badan kurang pada balita (OR= 3,5; CI= 1,118 – 10,962) (p-value <0,05). Hasil penelitian menyarankan pemerintah untuk lebih banyak terlibat untuk meningkatkan peran masyarakat seperti petugas puskesmas dan kader dalam pencegahan, pendeteksian, dan penanganan kasus anak dengan berat badan rendah dengan memberikan edukasi dan solusi pencegahannya.